Study of Consumer’s Unconscious Reaction towards the Use of Anthropomorphic Appearance of AI: An Eye-tracking Experiment - Ene, Irina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
With disruptive technologies constantly emerging, the impact of artificial intelligence is becoming a relevant topic nowadays. An extensive investment in business intelligence support systems has been recognized as one of the top priorities of most successful managers. However, these constant internal changes of systems and management styles rarely happen smooth and natural, and frequently they trigger serious issues for the companies and its interactions with their customers. Implementations like automated call centers and online payment systems are just mainstream examples which can be used to show the numerous implications of the intrusion of artificial intelligence systems in our everyday life. With the increasing use of various forms of technology, an ongoing discussion has emerged about people's willingness to accept these technological trends. There are, of course, both pro and counter arguments to be discussed. In this article there are presented the results of an eye-tracking experiment about the reaction of consumers towards several forms of artificial intelligence. It has been shown that consumers have the tendency to react more at unexpected situations involving robots and forms of artificial intelligence.